Serious Intestinal Diseases Parasitism. A case presentation. - Rubén Bembibre Taboada; Magalys Olivert Cruz; Pedro Juan Barrios Fuentes (Medisur)
In countries with developed health systems as ours, the report of parasitic diseases with torpid evolution is very rare. When they occur, they are rapidly detected and treated and thus don’t become death causes. A case is presented of a 32 year old woman to whom a poliparasitismo caused her to die.